Non-Return and Non-Arrival in Aboriginal Australia. Comment on Isayev (2021). Ancient Wandering and Permanent Temporariness. Humanities 10: 91 - Paul Magee; Paul Collis (Humanities, 2022)
This dialogue constitutes an engagement with Elena Isayev’s article, “Ancient Wandering and Permanent Temporariness”. It focusses on concepts Elena has marshalled for the analysis of ancient and contemporary experiences of displacement (“non-return”, “non-arrival”, “permanent temporariness”) within what are largely international political frameworks. The point of our response is to see what happens when we apply these concepts to Aboriginal people’s experiences of displacement within the Australian nation—a country that did not even count the indigenous as citizens until 1967. Some striking parallels emerge, in relation to how a people can be forced to live in a temporary state, their lives “made in between”. Our response took the form of a conversation and was recorded on 6 December 2021. We choose to speak and transcribe these thoughts, rather than write them, as a way to maintain the dialogic mode (a.k.a. “yarning”) in which Aboriginal intellectual work has flourished for millennia now. Towards the end of the exchange Paul Collis suggests that not only Aboriginal people, but the land itself, suffers from a kind of “permanent temporariness”.